Effect of Herb Treatments on the Storability of Sweet Oranges (Citrus sinensis Osberk) Stored in Evaporative Cooler - Adekalu, O A; Agboola , D A (Journal of Postharvest Technology, 2015)
Large quantities of oranges produced in Nigeria are wasted during storage. Sweet oranges due to their perishable nature deteriorate fast. Causes of spoilage are rather physiological or pathological factors. There is need for research breakthrough to minimize or reduce the post harvest losses encountered by orange farmers in Nigeria. Thymus vulgaris (Thyme), Allium sativum (Garlic), Cympobogon citratus (lemon grass) and Eugenia aromatica (Clove) aqueous extracts were prepared and used to treat oranges before storage in evaporative coolers. Harvested matured green oranges were dipped inside 5, 10, and 15% aqueous extracts each and air dried. The treated sweet oranges were stored inside Tin in Pot cooler A and Pot in Pot cooler B evaporative coolers. Percentage of ripening of sweet oranges was 40% and 45% for each cooler, while control was 100% at the end of the week. The treated oranges stored for between 35 to 52 days. Sensory evaluation, marketability, and acceptability were rated good at the end at the end of the study.